Makna Qana’ah dan Implementasinya di Masa Kini - Malikhatul Kamalia; Halimatussa’diyah; Anggi Wahyu Ari (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2022)
This research aims to find out the Meaning of Qana'ah in the Qur'an and Its Implementation In the Present (Tafsir Tahlili QS Study. Al-Hajj[22]: 36). Qana'ah is often misunderstood by resignedly accepting what it is without maximum effort and halal. This can be seen the rise of suicide cases caused by debt and increasing cases of corruption shows a person is dissatisfied with what they have and lack of spiritual, moral and moral understanding in society to prevent such behavior by means of religious. Lafazh qana'ah is mentioned once in the Qur'an, namely lafazh al-qani'. This research uses a qualitative approach based on literature (library research). The formulation of the problem of how the nature of qana'ah means in QS. Al-Hajj[22]: 36? How is qana'ah in the life of the Prophet and his depletion in the present? The method of interpretation used is the tahlili method in QS. Al-Hajj[22]: 36. The result of this study is the word qana'ah mentioned in the Qur'an with lafazh al-qani' meaning a fakir who accepts with satisfaction and sincerity for the sustenance that Allah has given and refrains from asking others. Qana'ah in the life of the Prophet (peace be upon him) is to choose a simple way of life, accept the circumstances faced and accept whatever is owned and not greedy whether the issue of wealth, rank, honor or other. The implementation of qana'ah in the present is by maximizing in trying (working) patiently and surrendering to Allah. Ask God for additional sustenance and caution against the luxuries of the world. Then everything that has been tried is received with satisfaction and gratitude to God and utilized according to needs.